The Effect of Competence: Intellectual, Emotional, and Social on Employee Performance with Adaptability as a Mediation Variable (Universitas Mercu Buana, 2022)
During the Covid-19 outbreak, the courier service industry played a critical role. In the face of this pandemic, businesses require personnel who are capable of surviving.Objectives: The goal of this study is to look at the direct impact of intellectual, emotional, social, and adaptability on employee performance, as well as the indirect impact of intellectual, emotional, and social competence on employee performance via adaptability.Methodology: This study adopts a quantitative methodology, data collection through a questionnaire, and obtained responses respondents (n = 98) from 113 respondents who have work experience in their field. The measurement model and hypothesis testing were carried out using the SmartPLS software.Finding: The results revealed that social competence and job satisfaction had a favorable and significant influence on employee performance, but intellectual and emotional competence had no such effect.Conclusion: The effect of social competence on employee performance might be mitigated through adaptability. Social competence and adaptability are important factors in boosting employee effectiveness. Further research can improve the research model and produce a broader research object so that it can assess intellectual and emotional competency so it is significant to employee performance.